PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN LOGISTIK PADA PT. LEX INDONESIA HUB SUKAMAJU (SJU) - Genta Aditya Farhan; Laila Irawati (Jurnal Publikasi Manajemen Informatika, 2026)
One of the keys to a company's success is human resource management. This study aims to analyze the influence of competence and work motivation on the performance of logistics employees at PT. Lex Indonesia Hub Sukamaju. This study uses a descriptive research methodology with a quantitative approach. Data collection for this study uses questionnaires supported by documentation studies. There were 80 employees who participated in this study. This study found that competence and work motivation have a positive and significant effect on employee performance. The regression analysis produced a simultaneous correlation coefficient of 0.927, which indicates a strong relationship between competence and work motivation and employee performance. In addition, the coefficient of determination value of 0.859 indicates that the two variables can describe 85.9% of the influence on employee performance, while the remaining 14.1% is influenced by other factors not included in this study. The results of the simultaneous hypothesis test produced an Fcount value of 234.673, indicating that competence and work motivation together significantly influence the performance of logistics employees at PT. Lex Indonesia Hub Sukamaju.